PENGARUH MOTIF PENGGUNAAN MEDIA TERHADAP KEPUASAN ANGGOTA WHATSAPP GROUP NEW WAVE INTERNATIONAL MINISTRY - Tang Natasha Chrisanti Saputra; Siti Meisyaroh (Jurnal Komunikasi dan Bisnis, 2019)
Humans as social beings communicate for various purposes, in this global era, online media is the choice for audiences when compared to other media. One of the most important communication media in Indonesia is WhatsApp with the WhatsApp group feature for group communication. The theory used is the Theory of Uses and Gratifications which examines the effect of media use. The method approach used in this study is quantitative by explanatory survey and using saturated sampling or census sampling techniques by distributing questionnaires to 113 respondents who are members of the WhatsApp group New Wave International Ministry. The influence of the motives of personal relationships has a considerable influence on the satisfaction of WhatsApp group members New Wave International Ministry, while the motives of surveillance, motives of personal identity and motives of diversity have sufficient influence on the satisfaction of WhatsApp members in the New Wave International Ministry. Keywords: Motive, Satisfaction, WhatsApp group